Infections, medication use, and the prevalence of symptoms of asthma, rhinitis, and eczema in childhood. Issue 10 (13th September 2004) - Cohet, Catherine; Cheng, Soo; MacDonald, Claire; Baker, Michael; Foliaki, Sunia; Huntington, Nyk; Douwes, Jeroen; Pearce, Neil
Abstract : Background: The "hygiene hypothesis" postulates that infections during infancy may protect against asthma and atopy. There is also some evidence that antibiotic and/or paracetamol use may increase the risk of asthma. Methods: The study measured the association between infections, and medication use early in life and the risk of asthma at age 6–7 years. It involved 1584 children who had been notified to public health services with serious infections at age 0–4 years, and 2539 children sampled from the general population. For both groups, postal questionnaires were completed by parents. Results: There was little difference in the prevalence of current wheezing between the childhood infections group (prevalence  =  23.5%) and the general population group (prevalence  =  24.3%). There was also little difference whether the major site of infection was gastrointestinal (prevalence  =  24.1%), invasive (prevalence  =  24.6%) or respiratory (prevalence  =  21.1%). However, in both groups, there were associations with antibiotic (OR = 1.78, 95% CI 1.49 to 2.14) or paracetamol (OR = 1.38, 95% CI 1.04 to 1.83) use in the first year of life or recent paracetamol use (OR = 2.10, 95% CI 1.78 to 2.49) and current wheezing. There was a weak protective effect of childhood infections in children who had not used antibiotics in the first year of life (OR = 0.78, 95% CI 0.55 to 1.10). Conclusions: These findings are consistent with other evidence that antibiotic use early in life may increase the risk of asthma. They are also consistent with some preliminary evidence associating paracetamol use with an increased risk of asthma. Any protective effect of notifiable childhood infections was weak.